SDGs-based adaptive curriculum model to improve education quality in the digital age - Eva Puspitasari (Himpunan Pengembang Kurikulum Indonesia, 2025)
The rapid advancement of technology and global sustainability issues demand innovations in educational curricula aligned with the Sustainable Development Goals (SDGs), specifically SDG 4 on quality education. This article examines the development of an adaptive curriculum model based on SDGs designed to enhance education quality in the digital era. Emphasizing 21st-century skills, such as critical thinking, creativity, collaboration, and digital literacy, this model prepares students to respond more to global challenges. The research employs a descriptive qualitative approach through a literature review, analyzing sources related to SDG implementation in education. Findings indicate that integrating technology into the curriculum enables more inclusive and interactive learning, reaching students in remote areas. The Project-Based Learning (PjBL) and Problem-Based Learning (PBL) approaches adopted in this curriculum have proven effective in enhancing students' skills in solving real-world problems. In conclusion, this SDG-based adaptive curriculum model has the potential to create a generation that is not only academically competent but also socially aware and sustainability-oriented, providing essential skills for navigating dynamic global changes. Abstrak Perkembangan teknologi yang pesat dan isu keberlanjutan global menuntut adanya inovasi dalam kurikulum pendidikan, yang relevan dengan Sustainable Development Goals (SDGs), khususnya SDG 4 tentang pendidikan berkualitas. Artikel ini mengkaji pengembangan model kurikulum adaptif berbasis SDGs yang dirancang untuk meningkatkan kualitas pendidikan di era digital. Dengan menekankan pada keterampilan abad 21, seperti berpikir kritis, kreativitas, kolaborasi, dan literasi digital, model ini bertujuan untuk mempersiapkan peserta didik agar lebih responsif terhadap tantangan global. Metode penelitian menggunakan pendekatan deskriptif kualitatif melalui studi pustaka, yang menganalisis sumber literatur terkait penerapan SDGs dalam pendidikan. Hasilnya menunjukkan bahwa integrasi teknologi dalam kurikulum memungkinkan pembelajaran yang lebih inklusif dan interaktif, serta menjangkau peserta didik di daerah terpencil. Pendekatan Project-Based Learning (PjBL) dan Problem-Based Learning (PBL) yang diadopsi dalam kurikulum ini terbukti efektif dalam mengasah keterampilan peserta didik dalam memecahkan masalah nyata. Kesimpulannya, kurikulum adaptif berbasis SDGs ini berpotensi menciptakan generasi yang tidak hanya cakap secara akademis, tetapi juga berkesadaran sosial dan berorientasi pada keberlanjutan, yang menjadi modal penting dalam menghadapi perubahan global yang dinamis. Kata Kunci: era digital; kurikulum adaptif; Sustainable Development Goals (SDGs)